Green in Gridlock : Common Goals, Common Ground, and Compromise - Hansen, Paul, 1952- (Book collections on Project MUSE., 2013)
Facing one of the most dangerous conservation crises in history-acid rain-lawmakers, industry leaders, and activists embraced an attitude of civil engagement that sought common ground and acceptance of compromise solutions on all sides. As a result, they achieved a spectacular outcome. This approach was also at work when another planet-threatening event-ozone depletion-was reversed. In Green in Gridlock, Paul Walden Hansen, the former head of the Izaak Walton League, takes stock of what has been accomplished and what has been squandered in the many environmental contests in.